Pulmonary carcinoids – analysis of early and long-term surgical treatment outcomes in a group of 90 patients - Kasprzyk, Mariusz; Musiałkiewicz, Jan; Kolasiński, Mikołaj; Jagiełka, Kajetan; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Over the years, pulmonary carcinoids have been treated as locally malignant tumors because of the favorable prognosis. It is currently known that the clinical course of the disease is mainly dependent on the carcinoid subtype. Aim : To analyze the early and long-term surgical treatment outcomes for typical and atypical carcinoids. Material and methods: A total of 90 patients were treated surgically for pulmonary carcinoid tumors in the years 2007–2015. Typical carcinoids were diagnosed in 69 (77%) cases, while atypical carcinoids – in 21 (23%); 67 patients underwent lobectomy, 3 – sleeve lobectomy, 9 – bilobectomy, 2 – pneumonectomy, 1 – segmentectomy, and 8 – wedge resection. Results : None of the patients died in the postoperative period. Complications occurred in 14.4% of patients. The most common complications included: arrhythmias (5.6%), prolonged air leak (3.3%), and residual pneumothorax (3.3%). Among the 21 patients with atypical carcinoids, N1 metastasis was found in 1 (4.8%) patient, while N2 – in 5 (23.8%) patients. In the group of 69 patients with typical carcinoids, N1 metastasis was revealed in 7 (10.1%) patients and N2 metastases – in 2 (2.9%) patients. The probability of 5-year survival in patients with typical and atypical carcinoids was 96% and 83%, respectively. During the follow-up period 7 (7.8%) patients, including 6 with atypical carcinoids, experienced local recurrence; distant metastasis occurred in 8 (8.9%) cases, including 6 with atypical carcinoids. Conclusions : Although radical surgical treatment provides excellent long-term outcomes, it should be noted that patients with pulmonary carcinoids (especially with the atypical subtype) may experience local recurrence and distant metastases even many years after surgery.